2015
DOI: 10.1080/13504509.2015.1004379
|View full text |Cite
|
Sign up to set email alerts
|

Applying contingent valuation to measure the economic value of forest services: a case study in Northern Jordan

Abstract: This paper reports an attempt to apply the contingent valuation method (CVM) to value ecosystem services in Jordan's northern forests. I employed the CVM to obtain an estimate for the population's willingness to pay (WTP) for restoration and conservation of services in this area. I sampled 300 rural households through in-person interviews, then applied two econometric models to examine the incentives for WTP. The aggregate present value benefit is 3,569,556 Jordanian Dinar for the whole of Jordan's northern fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
15
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(17 citation statements)
references
References 39 publications
2
15
0
Order By: Relevance
“…On the other hand, for income variables, a positive coefficient value suggested that the higher the household income, the greater the WTD for forest conservation and management. This conclusion is supported by another study, which illustrated that forest service type and income significantly influenced participants' willingness to pay for forest conservation (Al-Assaf., 2015).…”
Section: Probit Regression Analysissupporting
confidence: 52%
“…On the other hand, for income variables, a positive coefficient value suggested that the higher the household income, the greater the WTD for forest conservation and management. This conclusion is supported by another study, which illustrated that forest service type and income significantly influenced participants' willingness to pay for forest conservation (Al-Assaf., 2015).…”
Section: Probit Regression Analysissupporting
confidence: 52%
“…Similarly, degradation of forests is likely to result in livelihood loss for forest-dependent households which further explain their higher WTP (Gatiso, 2019). Similar findings have been reported in Jordan where collection of forest products such as wild plants positively influenced WTP for forest services (Al-Assaf, 2015). These findings suggest that households involved in forest extraction have a higher likelihood to contribute both in-cash or labour for conservation of the resource.…”
Section: Resultssupporting
confidence: 87%
“…ESs provide direct benefits as well as indirect services, including the provision of food, water, and raw materials; the regulation services of fresh air and pure water; and aesthetic and spiritual attractions [2,3]. Studies on ESs values have been conducted at different scales from the national, regional, and global scales and in diverse areas, including forest, desert, wetland, and growing urbanizing areas [4][5][6][7]. Researchers have provided sufficient evidence indicating that many important ecosystems are facing threats of degradation, mostly attributed to climate change and population growth, which reflects the importance of valuing their impacts on ES within decisionmaking processes [8,9].…”
Section: Introductionmentioning
confidence: 99%
“…Presently, ESs are considered in the land management and decision-making process, which has helped in shaping the national projects in ecological development and urbanization or civilization [13]. Several studies have addressed ESs at the different geographic zones; for instance, studies were conducted to examine and value the ESs in forest ecosystems [5,6,[14][15][16]. Other national studies were conducted to estimate the ES value in arid areas (e.g., Wadi Araba (WA) in south-west Jordan), which demonstrated that WA harbors many valuable genetic plant resources that can be used for many purposes, including food, feed, energy, aesthetics, fiber, and medical.…”
Section: Introductionmentioning
confidence: 99%